Understanding positive prevention practices among people living with HIV in Karnataka, Southern India - R, Manjunatha (Australasian Medical Journal, 2011)
BACKGROUND: Understanding positive prevention practices among people living with HIV (PLHIV) can provide useful insights to guide our efforts in preventing further HIV transmission, and helps to enable PLHIVs to lead healthy and responsible lives. METHOD: A cross-sectional study was conducted in three sites of Karnataka: namely Belgaum (North Karnataka), Bellary (Central Karnataka) and Hassan (South Karnataka) districts. The study period was from March to September 2010. A total of 477 PLHIV were sampled and interviewed with the help of a structured interview schedule. The interviews were conducted by trained PLHIV community interviewers. RESULTS: Disclosure of status was fairly good among the studied population. The majority of men disclosed their HIV status first with their spouses, whereas women disclosed first with their mothers. Status disclosure was less among urban PLHIV when compared to rural PLHIV. Knowledge about Sexually Transmitted Infections (STIs) among unmarried men and women was low; higher proportions among them were involved in sexual relationships; and they reported no condom use with their regular partners. Condom use with regular partners is found to be more effective when public health messages are given through peers. Status disclosure is having a role in motivating communities for Regular CD4 testing and ART uptake. CONCLUSION: Unmarried PLHIV need to be prioritised in our prevention efforts, to enable them to adopt safe sex practices through appropriate peer-mediated strategies. As status disclosure with family members has an important role in adhering to ART, status disclosure with family members needs to be emphasized in our programmes.